Wang-Landau algorithm for entropic sampling of arch-based microstates in the volume ensemble of static granular packings - Slobinsky, Demian Gustavo (2015)
We implement the Wang-Landau algorithm to sample with equal probabilities the static configurations of a model granular system. The “non-interacting rigid arch model" used is based on the description of static configurations by means of splitting the assembly of grains into sets of stable arches. This technique allows us to build the entropy as a function of the volume of the packing for large systems. We make a special note of the details that have to be considered when defining the microstates and proposing the moves for the correct sampling in these unusual models. We compare our results with previous exact calculations of the model made at moderate system sizes. The technique opens a new opportunity to calculate the entropy of more complex granular models.